2018
DOI: 10.1523/jneurosci.0375-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

DMRT5, DMRT3, and EMX2 Cooperatively RepressGsx2at the Pallium–Subpallium Boundary to Maintain Cortical Identity in Dorsal Telencephalic Progenitors

Abstract: Specification of dorsoventral regional identity in progenitors of the developing telencephalon is a first pivotal step in the development of the cerebral cortex and basal ganglia. Previously, we demonstrated that the two zinc finger and () genes, () and , which are coexpressed in high caudomedial to low rostrolateral gradients in the cerebral cortical primordium, are separately needed for normal formation of the cortical hem, hippocampus, and caudomedial neocortex. We have now addressed the role of and in cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 67 publications
5
31
0
Order By: Relevance
“…Recently, Desmaris et al have reported a similar defect of dorsalventral patterning in Dmrt3/Dmrt5 and Emx2/Dmrt5 double mutants (Desmaris et al, 2018). This study is consistent with their previous report that Emx2 is a possible target of Dmrt5 (Saulnier et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…Recently, Desmaris et al have reported a similar defect of dorsalventral patterning in Dmrt3/Dmrt5 and Emx2/Dmrt5 double mutants (Desmaris et al, 2018). This study is consistent with their previous report that Emx2 is a possible target of Dmrt5 (Saulnier et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…The reason for this decrease could be related to developmental impairment of the medial part of the telencephalon. In accordance with the present results, previous studies have demonstrated malformation of caudomedial telencephalic structures in Dmrta2 and Dmrt3 KO mice . A question thus arises: when is the onset of defects in the medial telencephalon in Dmrt mutants?…”
Section: Discussionsupporting
confidence: 92%
“…It is reported that migration of CH‐derived CR cells to the lateral region in the cortex are regulated by guidance cues from the meninges and neurons derived from the neocortex . Since the neocortical area‐patterning and neurogenesis in Dmrt mutants are affected in depending on the Dmrt dosages, the neocortex lacking function of Dmrt may be an inhospitable environment for their migration.…”
Section: Discussionmentioning
confidence: 99%
“…There, the gene is inter alia expressed in the central nervous system (CNS), nasal placodes, Müllerian ducts, forming somites, and the developing gonads (e.g. [66] Smith et al 2002, [67] Winkler et al 2004, [68] Desmaris et al 2018, [69] Yan et al 2018).…”
Section: Discussionmentioning
confidence: 99%